Effect of use of Different Levels of Zingiber officinale on Production ‎‎,blood traits and Liver enzymes in Awassi Ewe’s Blood‎ - A.Al-Khayat, ‎ Dhia; M.M. Zakri, Ahmed (The Iraqi Journal of Veterinary Medicine, 2010)
This research was designed to study the effect of tow levels of Zingiber officinale on Body weight , Hb , PCV ,WBCs account , Lymphocytes , Neutrophiles accounts GOT and ALP liver enzymes in Awassi ewe’s blood , Nine Awassi ewes aged 1.5 years were divided into 3 equal groups as followed : Group A was treated by 10 gm Zingiber officinale / animal /daily (2.5%) of diet While group B were treated with 20 gm Zingiber officinale / animal daily (5%) of diet and group C considered as Control group without given Zingiber officinale with diet ,the results showed that significant increase (P<0.05)on body weight in treatment B during weeks of trail compare with the groups A & C . also in blood traits there was a significant increase (P<0.05) in PCV, Hb, WBCs ,Lymphocytes accounts in group B during weeks of trail compare with the groups A & C while there was significant decrease (P<0.05) in Neutrophile accounts in group B during weeks of trail compare with the treatments A &C, there was significant decrease (P<0.05)on GOT (Glutamic Oxaloacetic Transminase) level in group B compare with the groups A & C. While there was a significant increase (P<0.05) on ALP (Alkaline Phosphatase) in group B compare with the groups A&C. We conclude that 20 gm / animal (5%) of diet increase body weight ,blood traits & Liver enzyme ALP in compared with other groups